2004
DOI: 10.1093/ndt/gfh423
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed T-cell activation by IFN- -induced expression of PD-L1 on renal tubular epithelial cells

Abstract: These data demonstrate that PD-L1 is an inducible renal tubular epithelial antigen that negatively regulates T-cell responses elicited by IFN-gamma-stimulated TEC. We speculate that the PD-1/PD-L1 pathway may play a role in protecting the epithelium from immune-mediated tubulointerstitial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
72
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 22 publications
8
72
1
1
Order By: Relevance
“…T cells causing tubulointerstitial injury in allograft rejection [11], and also PD-L1 is strongly up-regulated by TECs in rejected kidney transplants as well as in inflamed kidneys [12][13][14]. While in the present case PD-L1 expressions in renal tubular cells were not recognized in spite of interstitial massive CD3…”
Section: Discussioncontrasting
confidence: 53%
“…T cells causing tubulointerstitial injury in allograft rejection [11], and also PD-L1 is strongly up-regulated by TECs in rejected kidney transplants as well as in inflamed kidneys [12][13][14]. While in the present case PD-L1 expressions in renal tubular cells were not recognized in spite of interstitial massive CD3…”
Section: Discussioncontrasting
confidence: 53%
“…We have previously shown that PD-L1 is expressed on endothelial cells and inhibits T cell activation (20). In addition, PD-L1 is expressed on microvascular endothelial cells (21,33) as well as on pancreatic islet cells (31) and tubular epithelium (34). Although we found PD-L1 in the neointima of atherosclerotic lesions, this likely reflects expression on lesional DCs or macrophages.…”
Section: Discussionmentioning
confidence: 49%
“…1D) (13,30,31). As a next step, we evaluated donor cell inhibitory signal ligands and PD-L1 expression in host tissues after BMT.…”
Section: Resultsmentioning
confidence: 99%